Incidental Discovery of Multiorgan Extramedullary Plasmacytomas in the Setting of Newly Diagnosed Multiple Myeloma and Delayed Hemolytic Transfusion Reaction - Joselle Cook; Steven Song; Anthony Ventimiglia; Carol Luhrs (Case Reports in Hematology)
Extramedullary plasmacytomas (EMPs) are defined by the presence of clonal plasma cell proliferation outside of the bone marrow, portending an overall poor prognosis. This case highlights extramedullary plasmacytomas as an unusual presenting manifestation of multiple myeloma. Through incidental discovery during a delayed hemolytic transfusion reaction workup, EMPs were found in the liver, spleen, and possibly the lung. Though rare at presentation, this case emphasizes that the presence of EMPs should be considered at the outset as it not only impacts the treatment regimen for such patients but also considerably affects prognosis.